Tapioca starch-pullulan interaction during gelation and retrogradation. (October 2018) - Sheng, Long; Li, Peishan; Wu, Huiqing; Liu, Yuanyuan; Han, Ke; Gouda, Mostafa; Tong, Qunyi; Ma, Meihu; Jin, Yongguo
Abstract: The interaction between pullulan (PU) and tapioca starch (TS) during gelatinization and retrogradation was studied in this paper. TS and PU were prepared into a TS/PU composite system at the ratios of 10/0, 9.5/0.5, 9.0/1.0, 8.5/1.5 and 8.0/2.0 g/g. The addition of PU tended to decrease the peak, breakdown and final viscosity of the composite system. The increasing tanδ of the dynamic viscoelastic measurement suggested that PU enhanced the liquid-like properties of TS gels. The decreased setback values and the slower increase of the storage modulus at 4 °C indicated that the short-term retrogradation of TS was restrained. Meanwhile, the peaks of X-ray diffraction became lower and wider, revealing that PU could inhibit the long-term retrogradation of TS. The FTIR spectra showed that the absorption peak of the O−H stretching gradually redshifted with increasing PU content, suggesting that a strong intermolecular hydrogen binding occurred between TS and PU. From low-field nuclear magnetic resonance, the spin-spin relaxation time decreased from 1687 ms (TS/PU = 10.0/0) to 1427 ms (TS/PU = 8.0/2.0), illustrating that the addition of PU promotes the water retention ability of the TS paste. Therefore, PU had an effect on TS gelatinization and retrogradation. Highlights: Pullulan can reduce the peak viscosity during gelatinization process. Pullulan restrains the short- and long-term retrogradation of starch. Intermolecular hydrogen bonding occurs between starch and pullulan. Pullulan promotes the water retention ability of tapioca starch paste.